2018
DOI: 10.1159/000495922
|View full text |Cite
|
Sign up to set email alerts
|

Coccomyxa Gloeobotrydiformis Polysaccharide Inhibits Lipopolysaccharide-Induced Inflammation in RAW 264.7 Macrophages

Abstract: Background/Aims: Inflammation plays a vital role in the etiology and pathogenesis of chronic noncommunicable diseases (NCDs), which are the leading health issues throughout the world. Our previous studies verified the satisfactory therapeutic effects of Coccomyxa gloeobotrydiformis (CGD) polysaccharide on several NCDs. In this study, we aimed to investigate the anti-inflammatory effects of CGD polysaccharide, and the corresponding molecular mechanisms, on lipopolysaccharide (LPS)-induced inflammation in RAW264… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 39 publications
3
24
0
1
Order By: Relevance
“…Pretreatment with Ls-ME suppressed the reduction in cell viability ( Figure 1 C). With respect to the morphology of activated macrophages, the LPS-treated group demonstrated an altered shape in comparison with the untreated group [ 22 ]. The cells retained original round shape in the group that was subjected to pretreatment with Ls-ME despite stimulation with LPS ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment with Ls-ME suppressed the reduction in cell viability ( Figure 1 C). With respect to the morphology of activated macrophages, the LPS-treated group demonstrated an altered shape in comparison with the untreated group [ 22 ]. The cells retained original round shape in the group that was subjected to pretreatment with Ls-ME despite stimulation with LPS ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
“…Since NO and ROS are well-known pro-inflammatory mediators that play an essential role in the inflammatory process, the effects of Ls-ME on LPS-induced inflammatory response in RAW 264.7 cells were investigated by the detection NO levels and intracellular ROS production [22,23]. The generation of NO was remarkably enhanced in response to the stimulation with LPS.…”
Section: Ls-me Reduces No Ros and Tnf-α Productionmentioning
confidence: 99%
“…Immunofluorescence assay was applied to detect the expression with confocal spectral microscopy, as described previously 22 . RAW 264.7 cells were seeded onto glass coverslips overnight and treated with PIPO for 1 hour before incubating with LPS.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence assay was applied to detect the expression with confocal spectral microscopy, as described previously. 22 RAW 264.7 cells were seeded onto glass coverslips overnight and treated with PIPO for 1 hour before incubating with LPS. After exposure, cells were treated with cold 4% paraformaldehyde for 20 minutes and permeabilized using 0.5% Triton-X 100 for 30 minutes.…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
“…NF-κB transactivation is crucial for the upregulation of various pro-inflammatory cytokines, including tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) [ 10 ]. It has been reported that the Janus kinases-signal transducer and activator of transcription (JAK-STAT) protein signaling pathway is associated with increased pro-inflammatory mediators, such as inducible-nitric oxide synthase (iNOS), that produce nitric oxide (NO) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%